The generational impact of tawḥidic practices and propensities in architectural historiography: linking the notion of ‘Time’ in Sūrah al-ʿAṣr to architectural evolvements - Jahn Kassim, Puteri Shireen; Jamil, Khairil Husaini; Awang, Arita Hanim (Jabatan Usuluddin dan Falsafah, Universiti Kebangsaan Malaysia (UKM), 2018)
The notion of ‘time’ has been essentially delved upon and repeatedly forwarded in a range of perspectives and dimensions, based on the immutable yet meaningful depth of Surah al-ʿAṣr, the 103rd chapter of the Qurʾān. Rather than discussing its meaning as an individual principle of the undisputable value of time, the meaning of the chapter here is linked to the long-term generational impact of spiritual contact, i.e. tawhidic paradigm and its propensities, on either the Muslim or non-Muslim civilisation, from the dawn of Islam to the present day. This study argues that the sūrah implicitly sheds light into the impact of tawhidic and spiritual practices of observant societies upon its generations and its physical form of civilisations. Its art and architecture are inevitably linked as well to the impact of such practices. Furthermore, it has been forwarded that at certain periods of history, there were discernible peaks in the flowering or efflorescence of art and architecture, which were universally acknowledged and recognized. Yet these occur throughout different periods of the civilisational history. The aim of this article, therefore; is to highlight the related generational effects that were propelled by the height and practice of such belief systems which still uphold some notions of tawhidic values. Certain cases are investigated such as the rise of Islam in Spain which culminated in the magnificence of the Alhambra, the rise of the ‘prairie style’ in United States, and the Arts and Crafts movement and its spin-offs in United Kingdom. It has also been forwarded that the eventual demise of such inventiveness and soulful works is related to a gradual loss in tawhidic values and religiosity, which became acute after the end of the World Wars. The spiritual emptiness had also brought about the lack of soul and homogeneity in architecture and built form following the rise of modern architectural movements in the 21st century.